Efektifitas Ekstrak Etanol Kayu Siwak (Salvadora Persica L.) Dengan Metode Perkolasi Terhadap Pertumbuhan Sta phylococcus Aureus Isolat 248 Yang Resisten Multiantibiotik - Fatkhurrohman, Fuad; Medawati, Ana (Insisiva Dental Journal, 2013)
Siwak (Salvadore persica) is one of alternatif plant which contains antimicroba. Siwak wood contains subject of active antimicribial, such as saponin, terpenoid, and fenol which effective in killing and inhibiting some the growth of oral aerob and anaerob bactery also as non fungal. The research has purpose to search the effectivity of siwak wood etanol extract antibactery with percolation method to isolat 248 S. aureus growth to amicacyn, amoxicilyn, amphycilyin,eritromicyn, canamicyn, chloramphenicol, mesilynam, penicilyn G, sefepym,seltadizym, sefotacsym, seftriacson, sefurocym, and tetraciclyn. This research was experimental study (in vitro) in microbiology laboratory of Medical Faculty of Gadjah Mada University Yogyakarta, trough antibactery potention test of liquid dilution method. Siwak stick was made etanol extract using percolation method and made various concetration from 0, 09 up to 25%. Antibactery capacity was determined by measurement of minimal killing value measuarement was based on the smallest consentration which can be kill bactery continuously by observation the growing of isolat 248 S. aureus colony. The result shows that siwak wood etanol extract with percolation method has minimal killing value in 25% concentration to isolat 248 S. aureus.